RELEVAN COSTANALYSIS : DASAR PENGAMBILAN KEPUTUSAN MEMPRODUKSI SENDIRI ATAU MEMBELI - RIZKIYAH, RIZKIYAH; Rahayu, Yuliastuti (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research is meant to analyze the application of Relevant Cost as the instrument of decision making to produce or to purchase at CV. Perdana 2000 Surabaya. The data is done by using secondary and primary data.This research applies qualitative analysis case study method. The problem in this research is how the application of Relevant Cost as the instrument of decision making to produce or to purchase in order to maximize the profit that has been obtained and to minimize the risk. The data collection technique has been done by visiting directly to see the condition of the field in real in obtaining accurate sources of data. The field research is carried out by conducting interview, documentation and observation on staffs who are expert in their field at CV. Perdana 2000. Based on the result of the analysis and the discussion of relevant costs, it shows that CV. Perdana 2000 has not carried outcost analysisrelevantproperly. The result ofthe analysis of the relevant costs, particularly in decision making to purchase or produce it self shows that the decision to produce its own is more appropriate because it can obtain high profit. Meanwhile, the purchase decision, the profit is lower.Keywords:Relevant Cost, Decision Making to Purchase or Produce its Own, TheApplication of Relevant Cost